Recent trends in EU corporate demography and policy: COVID and beyond - Julien Brault (European Investment Fund (EIF), 2023)
This working paper examines recent trends in EU corporate demography and the role of policy responses during the COVID crisis. It compares recent bankruptcy and business creation rates to past trends. Pre-crisis trends were showing declining business creations and rising bankruptcies. After COVID, bankruptcy rates dropped, but recently rose significantly. The crisis had significant negative effects on business creation rates and total EU corporate population. The paper also correlates Member States' fiscal policy responses to the evolution in corporate demography. These tended to limit bankruptcies rather than foster business creations. Major divergences occur between countries, sectors, and types of firms. The paper underlines the necessity of policy actions supporting business creations.
Keywords: 330